Preparation and Characterization of Ag doped ZnO nanoparticles and its Antibacterial Applications - Srithar, A.; Kannan, J.C.; Senthil, T.S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In the present investigation, AgxZn1-xO nanoparticles (x = 0.05, 0.075, and 0.1%) have been successfully synthesized by precipitation method. The synthesized AgxZn1-xO nanoparticles were characterized by X-ray diffraction analysis (XRD), Field emission scanning electron microscopy (FESEM), Energy dispersive X-ray spectroscopy (EDX), High resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy and UV–visible spectrophotometer. The XRD studies revealed that the Ag doped ZnO nanoparticles in hexagonal wurtzite structure. The FESEM and HRTEM images show that the presence of aggregated nanoparticles. The EDX spectrum confirmed the present metals in AgxZn1-xO nanoparticles which indicated the purity of the sample. The FTIR and Raman spectrum indicates that the present functional groups and crystalline quality of Ag doped ZnO nanoparticles. The optical properties were measured by using UV–Vis Spectrophotometer. The antibacterial activity of the samples are examined and also compared with standard drugs.